Instrumentos jurídicos de pagamentos por serviços ambientais aplicados na política municipal de resíduos sólidos de materiais recicláveis urbanos - Schneider, Vanderlei (My University, 2025)
The research addresses the theme of the legal instrument of Payment for Environmental Services and the Municipal Policy on Solid Waste. It is delimited in relation to the issues involving the National Policy on Solid Waste and the National Policy on Payment for Environmental Services, at the municipal level. The research problem aims to clarify: How can the legal instruments of Payment for Environmental Services be applied in the municipal management of urban recyclable solid waste, promoting socio-environmental inclusion and efficiency in the recycling chain? The hypothesis raised is that the adoption of legal instruments of Payment for Environmental Services can contribute to making the chain of urban recyclable materials viable, by promoting economic incentives aimed at selective collection and adequate disposal of waste. The general objective is to propose basic elements, guidelines and reflections for a public policy of Payment for Environmental Services to make the chain of urban recyclable materials viable, within the scope of the municipal policy on solid waste. The specific objectives are: a) To critically analyze the relationship between humans and the environment; b) To examine the legal provisions of the PNRS applicable to solid waste management in municipalities; c) To discuss Payment for Environmental Services as a possible legal and economic instrument capable of fostering urban solid waste management; d) To evaluate the creation of a municipal public policy that implements the PSA focused on the urban recyclable materials chain. The approach used is hypothetical-deductive, and the procedure method adopted is bibliographic, involving documentary and normative analysis, detailed review of federal, state and municipal legislation related to the topic, in addition to contemplating the study of legal doctrine, articles, dissertations and theses. It was found that, although Law 12.305/2010, which institutes the National Solid Waste Policy, has been in force for over a decade, the objectives are still difficult to achieve and recycling continues to be a challenge. The recent Law 14.119/2021, which regulates the National Policy on Payment for Environmental Services, does not address issues related to solid waste, incentives for selective collection or collectors, nor does it mention remuneration for environmental services. Furthermore, although there is no clear legal framework, the research carried out revealed the potential of PSA as an innovative means of recycling solid waste, seeking to minimize environmental impacts that are crucial for improving the environment and sustainable urban development. It was concluded that the hypothesis was confirmed and it was found that the adoption of incentive policies such as the PSA legal instrument can be considered an alternative in the municipal policy for solid waste of recyclable materials. It was also identified that the PSA program seeks to motivate organized collectors, increasing selective collection and making the activity more attractive, among other measures. It is worth highlighting that the object of this research is socially relevant, environmentally necessary and academically does not end here, since the final descriptions suggest a proposal for the elaboration and implementation of a bill on Payment for Environmental Services in the chain of urban recyclable materials at the municipal level. [resumo fornecido pelo autor]
A investigação aborda o tema do instrumento jurídico de Pagamento por Serviços Ambientais e a Política Municipal de Resíduos Sólidos. Delimita-se em relação às questões que envolvem a Política Nacional de Resíduos Sólidos e a Política Nacional de Pagamento por Serviços Ambientais, em âmbito municipal. O problema da pesquisa visa esclarecer: Como os instrumentos jurídicos de Pagamento por Serviços Ambientais podem ser aplicados na gestão municipal de resíduos sólidos recicláveis urbanos, promovendo inclusão socioambiental e eficiência na cadeia da reciclagem? A hipótese levantada é que a adoção de instrumentos jurídicos de Pagamento por Serviços Ambientais pode contribuir para viabilizar a cadeia de materiais recicláveis urbanos, ao promover incentivos econômicos voltados à coleta seletiva e à destinação adequada dos resíduos. O objetivo geral é propor elementos básicos, diretrizes e reflexões para uma política pública de Pagamento por Serviços Ambientais para viabilizar a cadeia de materiais recicláveis urbanos, no âmbito da política municipal de resíduos sólidos. Os objetivos específicos são: a) Analisar criticamente a relação entre homem e meio ambiente; b) Examinar os dispositivos legais da PNRS aplicáveis à gestão de resíduos sólidos nos municípios; c) Discutir o Pagamento por Serviços Ambientais como um possível instrumento jurídico e econômico capaz de fomentar a gestão de resíduos sólidos urbanos; d) Avaliar a criação de uma política pública municipal que implemente o PSA voltada para a cadeia de materiais recicláveis urbanos. O método de abordagem utilizado é o hipotético-dedutivo, e o método de procedimento adotado é o bibliográfico, envolvendo a análise documental e normativa, revisão detalhada das legislações federais, estaduais e municipais relacionadas ao tema, além de contemplar o estudo da doutrina jurídica, artigos, dissertações e teses. Constatou-se que, embora a Lei 12.305/2010, que institui a Política Nacional de Resíduos Sólidos, esteja em vigor há mais de uma década, os objetivos ainda são difíceis de serem alcançados e a reciclagem continua sendo um desafio. A recente Lei 14.119/2021, que regulamenta a Política Nacional de Pagamento por Serviços Ambientais, não aborda questões relacionadas a resíduos sólidos, incentivos à coleta seletiva ou catadores, nem menciona remuneração por serviços ambientais. Ademais, embora não haja um arcabouço legal claro, a pesquisa realizada revelou o potencial do PSA como meio inovador por reciclagem de resíduos sólidos, buscando minimizar impactos ambientais crucial para a melhoria do meio ambiente e o desenvolvimento urbano sustentável. Conclui-se que a hipótese foi confirmada e constatou-se que a adoção de políticas de incentivo como o instrumento jurídico de PSA pode ser considerada uma alternativa na política municipal de resíduos sólidos de materiais recicláveis. Identificou-se também que o programa PSA busca motivar catadores organizados, aumentando a coleta seletiva e tornando a atividade mais atrativa, entre outras medidas. Vale destacar que o objeto desta pesquisa é socialmente relevante, ambientalmente necessário e academicamente não se esgota aqui, pois as descrições finais sugerem uma proposta de elaboração e implementação de um projeto de lei sobre Pagamento por Serviços Ambientais na cadeia de materiais recicláveis urbanos em nível municipal. [resumo fornecido pelo autor]
Keywords: Direito ambiental; Gerenciamento de resíduos; Desenvolvimento econômico - Aspectos ambientais; Política pública; Environmental law; Waste management; Economic development - Environmental aspects; Public policy